The Effect of Value Clarification Technique (VCT) Model Assisted by Canva Media on Motivation and Learning Outcomes of Pancasila Education - Saputri, Fara Kesyha Cahya; Astuti, Tri (Universitas Muhammadiyah Ponorogo, 2025)
Basic education is an important foundation in shaping the quality of human resources and determining the success of the next level of education. In the context of education in Indonesia, Pancasila Education has a strategic role in instilling character and national values from an early age. Unfortunately, the implementation of Pancasila Education learning at the elementary school level still faces two main problems, namely the lack of variety in the learning methods used and the low motivation of students to learn. This study examines the effect of using the Value Clarification Technique (VCT) model with Canva media on the motivation and learning outcomes of fourth grade students of SD Negeri Purwoyoso 04 Ngaliyan Semarang in the subject of Pancasila Education.. The VCT model was chosen because it is considered to be able to increase students' active participation through activities to find, analyze, choose, and decide on relevant values. The research approach used was quantitative experimental with a quasi-experimental design type of nonequivalent control group. Class IV A, totaling 23 people, became the experimental class sample and class IV B, totaling 23 people, became the control class sample. The tests used were pre-test and post-test. The results showed that the VCT model assisted by Canva media had an influence on the results and motivation of learning Pancasila Education in class IV. This result is indicated by the results of the t test of learning motivation sig of 0.001 0.05 and learning outcomes sig of 0.004 0.05, which means that there is a significant influence on the motivation and learning outcomes of Pancasila Education in Class IV SD Negeri Purwoyoso 04 Ngaliyan Semarang.